The global burden of rheumatoid arthritis: estimates from the Global Burden of Disease 2010 study. Issue 7 (18th February 2014) - Cross, Marita; Smith, Emma; Hoy, Damian; Carmona, Loreto; Wolfe, Frederick; Vos, Theo; Williams, Benjamin; Gabriel, Sherine; Lassere, Marissa; Johns, Nicole; Buchbinder, Rachelle; Woolf, Anthony; et al.
Abstract : Objectives: To estimate the global burden of rheumatoid arthritis (RA), as part of the Global Burden of Disease 2010 study of 291 conditions and how the burden of RA compares with other conditions. Methods: The optimum case definition of RA for the study was the American College of Rheumatology 1987 criteria. A series of systematic reviews were conducted to gather age-sex-specific epidemiological data for RA prevalence, incidence and mortality. Cause-specific mortality data were also included. Data were entered into DisMod-MR, a tool to pool available data, making use of study-level covariates to adjust for country, region and super-region random effects to estimate prevalence for every country and over time. The epidemiological data, in addition to disability weights, were used to calculate years of life lived with disability (YLDs). YLDs were added to the years of life lost due to premature mortality to estimate the overall burden (disability-adjusted life years (DALYs)) for RA for the years 1990, 2005 and 2010. Results: The global prevalence of RA was 0.24% (95% CI 0.23% to 0.25%), with no discernible change from 1990 to 2010. DALYs increased from 3.3 million (M) (95% CI 2.6 M to 4.1 M) in 1990 to 4.8 M (95% CI 3.7 M to 6.1 M) in 2010. This increase was due to a growth in population and increase in aging. Globally, of the 291 conditions studied, RA was ranked as the 42nd highest contributor to global disability, just below malaria and just above iodine deficiency (measured in YLDs). Conclusions: RA continues to cause modest global disability, with severe consequences in the individuals affected.